OPTIMALISASI KEGIATAN ORAGANISASI UNTUK MENINGKATKAN EFEKTIFITAS DALAM KELOMPOK KERJA - FITRI MARDIANA, LELY; WIASTONO, AGUS (JOURNAL KOPERASI DAN MANAJEMEN, 2025)
Purpose – The purpose is to optimize organizational activities to enhance effectiveness within work groups. This involves streamlining processes, improving communication, and fostering collaboration to maximize productivity and achieve shared goals. By strategically aligning resources and implementing best practices, we aim to create a more efficient and impactful work environment. Design/methodology/approach – This study employs a mixed-methods approach, combining quantitative data analysis of organizational activity metrics with qualitative interviews to identify key areas for optimization within work groups. The research focuses on streamlining workflows, enhancing communication channels, and improving resource allocation to demonstrably increase effectiveness and achieve organizational goals. The findings will provide practical recommendations for optimizing group activities. Findings – Optimization of organizational activities is crucial for enhancing workgroup effectiveness. Findings indicate that streamlining workflows, implementing clear communication channels, and fostering collaborative problem-solving lead to significant improvements in productivity and goal attainment. Furthermore, investing in targeted training and empowering team members to take ownership of their roles demonstrably increases efficiency and overall team performance. Research limitations/implications – This research on optimizing organizational activities to enhance workgroup effectiveness is limited by its specific contextual setting, potentially impacting generalizability to diverse organizational structures and cultures. Further research should explore the long-term sustainability of implemented interventions and examine the mediating roles of factors like communication and trust in achieving optimal workgroup performance across different industries and organizational sizes. These findings offer practical implications for managers seeking to improve team performance through targeted organizational adjustments, but should be adapted based on the specific needs of their teams. Originality/value – Optimizing organizational activities is crucial for enhancing effectiveness within workgroups. By streamlining processes, fostering clear communication, and aligning individual tasks with overarching goals, organizations can unlock significant productivity gains. Prioritizing strategic initiatives and eliminating redundancies ultimately leads to a more efficient and impactful work environment, maximizing the collective potential of the team.